2021
DOI: 10.2147/amep.s318560
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Based-Learning from Simple to Complicated Clinical Situations for Midwifery Students

Abstract: Purpose A health professional’s learning curriculum should lead to the acquisition of technical and non-technical skills. This study aims at demonstrating the impact of simulation-based learning (SBL) experience on the learning of midwifery students. Patients and Methods Using an experimental design, the experimental group (n=14) received pretest, high fidelity simulation, then a post-test. Whereas the control group (n=14) received pretest, revision of the theoretical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the past few years, the use of simulation has supplemented traditional nursing education [ 40 ]. This study outlined the creation of a VPS about DKA by incorporating the HSSOBP TM for Simulation Design and the MedicActiV platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, the use of simulation has supplemented traditional nursing education [ 40 ]. This study outlined the creation of a VPS about DKA by incorporating the HSSOBP TM for Simulation Design and the MedicActiV platform.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the use of simulation has supplemented traditional nursing education [40]. This study outlined the creation of a VPS about DKA by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to Changuiti et al, simulation has provided the opportunity for learning simple to complex clinical situations in a safe and semi-real environment for midwifery students [ 22 ]. In their systematic review, Yucel et al indicated that simulation, as an educational tool, improved the implementation of technical skills in educational and clinical environments.…”
Section: Discussionmentioning
confidence: 99%
“…To improve clinical competence, simulation-based learning can be used; a form of active pedagogy whereby simulated patient care scenarios helps learners acquire knowledge and skills that increase patient safety [ 21 , 22 ]. The evidence shows the knowledge enhancement experienced by students exposed to simulation-based learning, firmly establishing it as a cornerstone in refining healthcare providers’ practices [ 23 ]. The impact of student-centred simulation-based learning extends beyond the classroom, cultivating professional development and supporting learners in their transition from students to healthcare professionals [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of student-centred simulation-based learning extends beyond the classroom, cultivating professional development and supporting learners in their transition from students to healthcare professionals [ 24 ]. For midwifery students, this approach serves as more than just an educational tool; it becomes a transformative experience, fostering problem-solving and communication skills within an environment mirroring real-life situations, ultimately enhancing learning in a safe environment [ 23 , 25 ]. In addition, simulation-based learning is cost-effective when implemented in clinical settings [ 26 ] making it particularly beneficial for low-income settings.…”
Section: Introductionmentioning
confidence: 99%